Exposure-response analyses of efzofitimod in patients with pulmonary sarcoidosis - Gennyne Walker; Ryan Adams; Lauren Guy; Abhijeeth Chandrasekaran; Nelson Kinnersley; Pavithra Ramesh; Lu Zhang; Fran Brown; Vis Niranjan (Frontiers Media S.A., 2023)
Background: Preliminary evidence for efficacy in pulmonary sarcoidosis has been shown for efzofitimod. Here we present supportive evidence of efficacy based on an exposure-response analysis.Methods: Data from two studies (Phase 1, N = 24, single dose in healthy volunteers, and Phase 1b/2a, N = 25, multiple doses over 24 weeks in participants with pulmonary sarcoidosis) were used to build a population pharmacokinetic model. Using this model, the relationship between efzofitimod exposure and three prespecified efficacy parameters [mean daily oral corticosteroid (OCS) dose, percent-predicted forced vital capacity (ppFVC) and King's Sarcoidosis Questionnaire-Lung (KSQ-Lung) score] was explored. Linear regression described the relationship of efzofitimod exposure and OCS reduction, ppFVC and KSQ-Lung score. Logistic regression related efzofitimod exposure to the probability of achieving a minimal clinically important difference for ppFVC and KSQ-Lung score. Due to the small study size, trends (not statistical significance) in relationships are reported.Results: In patients with pulmonary sarcoidosis, as efzofitimod exposure increased, the mean daily OCS dose decreased, and ppFVC and KSQ-Lung score improved over baseline. The slope for all the endpoints by both linear and logistic regression showed an improving trend with increased exposure.Conclusion: These preliminary findings of a positive exposure-response across multiple efficacy endpoints support the claim that proof of concept has been established for the use of efzofitimod in pulmonary sarcoidosis.Clinical Trial Registration:clinicaltrials.gov, identifier NCT03824392